Behavior change interventions to address unhealthy food consumption: A scoping review - Kachwaha, Shivani; Kim, Sunny S.; Das, Jai K.; Rasheed, Sabrina; Gavaravarapu, SubbaRao M.; Rana, Pooja Pandey; Menon, Purnima (Elsevier, 2024)
High intakes of sodium, sugar, saturated fats, and trans fats contributed to 187.7 million disability adjusted life years (DALYs) from non-communicable diseases globally. Understanding of the global evidence on interventions to reduce consumption of various types of unhealthy food across diverse contexts is needed. We conducted a scoping review to examine the existing evidence on behavior change interventions (BCIs) to address unhealthy food consumption. Through a systematic search of 3 databases conducted in December 2022, 2,730 records were retrieved, and 145 studies met the eligibility criteria for review. Only 19% of the studies (n=28) were from low and middle-income countries. The key target group for most BCIs was adults ≥20 years (n=79). Interventions were conducted across 7 types of settings: schools (n=52), digital (n=30), community (n=28), home (n=14), health facility (n=12), worksite (n=6), and market (n=3). There were 4 mutually inclusive intervention types – information, education, and communication (IEC) (n=141); food/beverage substitution (n=10); interactive games (n=7); and labeling/warnings at point of purchase (n=3). The study outcomes included consumption of sugar-sweetened beverages (n=74), packaged salty snacks/fast food (n=61), sweets (n=43), and saturated fat (n=41). Drivers of food choice behaviors such as knowledge, attitudes, and beliefs; motivation and expectancies; and self-efficacy were reported in 43% of studies. Based on reported impact of BCIs on study outcomes, more interventions targeted at adults had positive impacts compared to those targeted at children; intervention packages including multiple IEC components also reported impacts more often than simple informational interventions. Interpretation of the findings was complicated by the lack of comparability in interventions, evaluation designs, outcome measures of unhealthy food consumption, duration of interventions, and study contexts. Future studies should invest in critical yet under-represented regions, examine behavioral determinants of unhealthy food consumption and the sustainability of behavior change, and conduct further analysis of effectiveness from experimental studies.